Antecedents of Job Satisfaction and Their Effect on Intention to Quit (Study on Professional Assistance Personnel (TPP) P3MD Central Java Province) - Shabrina Asmarani Aprilliana; Mirwan Surya Perdhana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The phenomenon encountered in the Professional Assistance Personnel (TPP) of the Village Community Development and Empowerment Program (P3MD) is the large number of people who have resigned from work, especially for the position of Local Village Facilitator (PLD). This is presumably due to a low level of job satisfaction. This study aims to analyze the effect of the antecedents of job satisfaction to intention to quit on PLD of Central Java Province. This study uses a mixed method approach with limitations. Quantitative and qualitative data collection was carried out using a questionnaire. The population of this research is all PLD in Central Java Province and the sample collected is 50. The results of this study break the hypothesis that job satisfaction has no effect on intention to quit. PLD feels that there are many things that make people dissatisfied at work, but that condition does not make them quit the job.